A Silicon Integrated Microwave Vector Network Analyzer for Biomedical Sensor Read-Out Applications - Nehring, Johannes; Nasr, Ismail; Borutta, Karl; Weigel, Robert; Kissinger, Dietmar (IEEE MTT-S International Microwave Symposium (IMS), 2014)
This paper proposes an integrated reflectometer for biomedical sensor read-out applications using a low-cost silicon- germanium technology. The heterodyne reflectometer consists of two integrated cross-coupled oscillators, a set of two directional couplers as well as Gilbert-Cell downconversion mixers. A dual phase-locked-loop architecture guarantees the phase lock of both on-chip signal sources to an external reference oscillator. An OSM-calibration was applied to the reflectometer and measure- ments of the complex reflection coefficient of an arbitrary device under test (DUT) showed excellent agreement with the results of a commercial vector network analyzer. As a proof of concept for sensor read-out, five solutions with different mixture ratios were characterized with a dielectric probe connected to the reflectometer.
elib2cris::1512001600,nehring2014

Design and Breakdown Behavior of 77GHz Variable Gain Power Amplifiers in SiGe- Technology - Borutta, Karl; Lämmle, Benjamin; Wagner, Christoph; Maurer, Linus; Weigel, Robert; Kissinger, Dietmar (European Microwave Conference (EuMC), 2013, 2013)
This paper presents two fully integrated differential programmable power amplifiers for automotive radar applications at 77GHz. The power amplifiers were fabricated in a silicon-germanium technology featuring bipolar transistors with an ft/fmax of 200GHz/250GHz. Measurements have been performed for different temperatures, in particular at -40°, 27° and 125°. A maximum gain of 10 dB is achieved for both amplifiers at room temperature. In addition the breakdown behavior of both amplifiers has been investigated. The building blocks of the amplifiers, which are affected by the breakdown effect had been indentified and design guidelines to avoid breakdown effects in power amplifiers are presented.
elib2cris::1512001600,borutta2013
Keywords: differential amplifiers; electric breakdown; millimetre wave bipolar transistors; millimetre wave power amplifiers; millimetre wave radar; programmable circuits; temperature measurement; Current measurement

Integrated Test Concepts for In-Situ Millimeter-Wave Device Characterization - Kissinger, Dietmar; Nehring, Johannes; Bauch, Andreas; Borutta, Karl; Nasr, Ismail; Lämmle, Benjamin; Weigel, Robert (IEEE 13th International New Circuits and Systems Conference (NEWCAS), 2015)
elib2cris::1512001600,kissinger2015b